Conjugate export pumps of the multidrug resistance protein (MRP) family: localization, substrate specificity, and MRP2-mediated drug resistance - König, Jörg; Nies, Anne; Keppler, Dietrich (Biochimica et biophysica acta. Biomembranes, 1999)
The membrane proteins mediating the ATP-dependent transport of lipophilic substances conjugated to glutathione, glucuronate, or sulfate have been identified as members of the multidrug resistance protein (MRP) family. Several isoforms of these conjugate export pumps with different kinetic properties and domain-specific localization in polarized human cells have been cloned and characterized. Orthologs of the human MRP isoforms have been detected in many different organisms. Studies in mutant rats lacking the apical isoform MRP2 (symbol ABCC2) indicate that anionic conjugates of endogenous and exogenous substances cannot exit from cells at a sufficient rate unless an export pump of the MRP family is present in the plasma membrane. Several mutations in the human MRP2 gene have been identified which lead to the absence of the MRP2 protein from the hepatocyte canalicular membrane and to the conjugated hyperbilirubinemia of Dubin-Johnson syndrome. Overexpression of recombinant MRP2 confers resistance to multiple chemotherapeutic agents. Because of its function in the terminal excretion of cytotoxic and carcinogenic substances, MRP2 as well as other members of the MRP family, play an important role in detoxification and chemoprevention.